Lurah’s Accountability For The Letter of Inheritance As Evidence - Intan Rizki Putriana; Tri Lisiani Prihatinah; Siti Muflichah; Antonius Sidik Maryono (Authentica, 2021)
Inheritance occurs because of the death of a family member. Currently, heirs can be limited with a Letter of Inheritance that can be made in the Kelurahan. This study aims to analyze the responsibility of the Lurah in making a Letter of Inheritance based on the inheritance system according to Islamic law in Indonesia. In addition, it is also aimed at analyzing the legal status of the Letter of Inheritance made by the Lurah as evidence. The research method used is normative juridical research. The results of the research, the Lurah and Camat are only administratively responsible in the process of recording the Letter of Inheritance, and are not responsible materially regarding the substance of the composition of Inheritaries. Other findings show that the Letter of Inheritance which was signed by the Petitioner legalized by the Head of the Village and the Camat, is an underhand letter.Keywords: Lurah, Letter of Inheritance, Islamic Law